Filamentous fungi from extreme environments as a promising source of novel bioactive secondary metabolites - Chávez, Renato; Fierro, Francisco; García-Rico, Ramón O.; Vaca, Inmaculada (Frontiers in microbiology, 2015)
Natural product search is undergoing resurgence upon the discovery of a huge previously unknown potential for secondary metabolite (SM) production hidden in microbial genomes. This is also the case for filamentous fungi, since their genomes contain a high number of "orphan" SM gene clusters. Recent estimates indicate that only 5% of existing fungal species have been described, thus the potential for the discovery of novel metabolites in fungi is huge. In this context, fungi thriving in harsh environments are of particular interest since they are outstanding producers of unusual chemical structures. At present, there are around 16 genomes from extreme environment-isolated fungi in databases. In a preliminary analysis of three of these genomes we found that several of the predicted SM gene clusters are probably involved in the biosynthesis of compounds not yet described. Genome mining strategies allow the exploitation of the information in genome sequences for the discovery of new natural compounds. The synergy between genome mining strategies and the expected abundance of SMs in fungi from extreme environments is a promising path to discover new natural compounds as a source of medically useful drugs.